DE LA REDACCIÓN A LA ESCRITURA ACADÉMICA - Miranda, Luis (2019)
This article focuses the problem in our country about students and teachers in general not being able to write an appropriate, correct and consistent piece of writing, discussing some key questions in order to overcome this language problem.